RELASI MASLAHAT MURSALAH DENGAN MAQOSHID SYARI’AH DALAM PENETAPAN HUKUM FIKIH - Ihsan Satrya Azhar (Tazkiya: Jurnal Pendidikan Islam, 2020)
This article aims the relationship between Maslahat Mursalah and Maqoshid Syari’ah and its application in fiqh. Even many Islamic scholars refuse to be said that they use Masalhat Mursalah independently, but actually they do so. Maqoshid Syari’ah is very important to Maslahat Mursalah as Maqoshid Syari’ah be come the guidance for it. Using maqoshid Syaria’ah will also avoid the scholars from just using the reason as the only tool in ijtihad. Using Maqoshid Syari’ah will also adjust the maslahat in it. Maqasid shariah provides the knowledge, understanding and justification for the principles of shariah. The aims of maqasid shariah is to benefit and protect the Ummah generally, and to discipline and structure the living in accordance with the Islamic values and principles as pronounced in the Quran and Sunnah. There are five objectives of Syariah : Protection of Faith or religion (din) Protection of Life (nafs) Protection of Lineage (nasl) Protection of Intellect ('aql) Protection of wealth (maal).Keywords: maslahat, the objectives of Syariah, ijtihad.